2016
DOI: 10.1002/cssc.201501595
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Porous Foam Loaded with Molybdenum Carbide Nanoparticulate Electrocatalyst for Effective Hydrogen Generation

Abstract: A facile method is developed for the synthesis of graphene porous foam (Gr PF) loaded with dispersed molybdenum carbide (Mo2 C) nanoparticles; the material exhibits effective catalytic activity in the hydrogen evolution reaction (HER). Mo2 C/Gr PF is synthesized by the carbonization of glucose and the carbothermal reduction of hexaammonium molybdate in a confined space defined by the intervals between sodium chloride nanoparticles. The synthesis in the confined space results in thin Gr PF (≈8 nm) loaded with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…The peak at 283.4 eV is from the carbon atoms bonded with molybdenum atoms . In addition, the two peaks located at 286 eV and 288.8 eV can be attributed to C=O and O−C=O, respectively. The oxygen component in the carbon matrix indicates the poor graphitization and disordering structure, which is unfavorable for the improvement of electrocatalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 283.4 eV is from the carbon atoms bonded with molybdenum atoms . In addition, the two peaks located at 286 eV and 288.8 eV can be attributed to C=O and O−C=O, respectively. The oxygen component in the carbon matrix indicates the poor graphitization and disordering structure, which is unfavorable for the improvement of electrocatalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Other than organic compounds, some inorganic salts such as evaporable scaffold-NaCl provide low-cost and effective templates toward sophisticated structures. [71] CO 2 emission during the heating process could effectively increase the surfacea rea by decreasing the size of the resultantM o x Cm aterials. [72] Furthermore, the selective etching of planar MXenetoprepare Mo x Ccomposites avoids the use of high temperature, even though the performance requires much improvementatt his stage.…”
Section: Organic-inorganic Hybrids Methodsmentioning
confidence: 99%
“…[81] Mo 2 Co n3 Dg raphene porousf oam exhibits as table hydrogen generation capabilityf or water electrolysis in both acidic and alkalines olutionw ith an early 100 %F aradic efficiency (Figure 5f). [71] Because of the similarity of electron structure between Mo x C and tungsten carbide( WC), the combination of Mo x Ca nd WC catalysta pplication is noticeable and practicable. Wang's group reported interwoven nanowires of WC backbone integrated with Mo 2 CN Ps by atomic affinity,w hich possess the average size of 15-20 nm.…”
Section: Mo X Cn Anoparticlesmentioning
confidence: 99%
“…Moreover,t he resultant TCNC spheres exhibit comparable HER catalytic activity with many other reported non-noble metal based catalysts toward HER catalysts, such as hierarchical b-Mo 2 Cn anotubes [11] and graphene/molybdenum carbide. [12] For comparison, the electrocatalytic activity of the samples obtained at different annealing temperatures and times is also investigated, and the results are shown in Figure S5. It can be found that the catalytic activity is initially enhanced asa nnealing temperature rises,w hile the further increaseo fa nnealing temperature leads to reduced catalytic activity.I na ddition, another interesting phenomenoni sa lso observed:a sa nnealing time prolongs, the catalytic activity is largely improved.…”
mentioning
confidence: 99%